The new world reader thinking and writing about the global community - Muller, Gilbert H. 1941-. (Boston, Massachusetts Houghton Mifflin, 2008)
With compelling selections by some of the world's most respected and critically acclaimed writers, The New World Reader encourages exploration of some of the most significant global challenges of the 21st century. Students consider topics that affect their lives, such as the challenges and consequences of globalization, global warming, bilingual education, and redefined gender roles. Challenged by such notable contemporary thinkers and writers as Richard Rodriguez, Bharati Mukherjee, Kwame Anthony Appiah, Kofi Annan, Barbara Ehrenreich, and Arundhati Roy, students develop their reading and critical-thinking skills. A consistent pedagogical apparatus includes brief chapter introductions, author headnotes, and pre-reading questions that offer students a preview of the central theme in each section. Exercise sets follow each essay, providing for writing, reading, discussion, and exploration opportunities.
Rhetorical Contents -- Thinking, Reading, and Writing About the New Global Era -- Critical Thinking -- Narration and Description -- Exposition -- Argument and Persuasion -- Thinking About an Essay: Nicholas D. Kristof, "Love and Race" -- Reading Critically -- Steps to Reading Critically -- Reading Visual Texts -- Reading an Essay Critically: Susan Bordo, "The Globalization of Eating Disorders" -- Writing in Response to Reading -- Prewriting -- Drafting -- Revision -- Writing in Response to an Essay: Lorraine Ali, "Not Ignorant, Not Helpless" -- New American Mosaic: Are We Becoming a Universal Nation? -- / Andrew Lam"All Things Asian Are Becoming Us" -- / N. Scott Momaday"The Way to Rainy Mountain" -- / Ishmael Reed"America: The Multinational Society" -- / Joseph Contreras"Two Americas?" -- / Bharati Mukherjee"American Dreamer" -- / Arthur Schlesinger Jr."The Cult of Ethnicity" -- / Moises Naim"Arabs in Foreign Lands" -- America and the World: How Do Others Perceive Us? -- / Fouad Ajami"Stranger in the Arab-Muslim World" -- / Alkman Granitsas"Americans Are Tuning Out the World" -- / Roger Cohen"An Obsession the World Doesn't Share" -- / Dominic Hilton"Fashionable Anti-Americanism" -- / Paul Johnson"America's New Empire for Liberty" -- / Anne Applebaum"In Search of Pro-Americanism" -- / Sasha Abramsky"Waking Up from the American Dream" -- Speaking in Tongues: Does Language Unify or Divide Us? -- / Amy Tan"Mother Tongue" -- / Chang-rae Lee"Mute in an English-Only World" -- / Mary Blume"If You Can't Master English, Try Globish" -- / Charles Foran"Lingua Franchise" -- / Ilan Stavans"Spanglish: The Making of a New American Language" -- / William H. Frey"Multilingual America" -- / Isabel Allende"Reading the History of the World" -- Global Relationships: Are Sex and Gender Roles Changing? -- / Lizette Alvarez"Arranged Marriages Get a Little Reshuffling" -- / Kofi A. Annan"In Africa, AIDS Has a Woman's Face" -- / Mohja Kahf"The Muslim in the Mirror" -- / Ellen Goodman"Justice for Women" -- / Azar Nafisi"The Veiled Threat" -- / Richard Rodriguez"Family Values" -- / Barbara Ehrenreich, Annette Fuentes"Life on the Global Assembly Line" -- The Challenge of Globalization: What Are the Consequences? -- / Thomas L. Friedman"Prologue: The Super-Story" -- / Pico Iyer"The Global Village Finally Arrives" -- / Johan Norberg"The Noble Feat of Nike" -- / Joseph S. Nye Jr."Fear Not Globalization" -- / Anthony Giddens"Globalisation" -- / Kwame Anthony Appiah"Toward a New Cosmopolitanism" -- / Benjamin Barber"The Educated Student: Global Citizen or Global Consumer?" -- Culture Wars: Whose Culture Is It, Anyway? -- / Barbara Ehrenreich"Cultural Baggage" -- / Mac Margolis"It's a Mall World After All" -- / Henry Louis Gates Jr."Whose Culture Is It, Anyway?" -- / Octavio Paz"Hygiene and Repression" -- / Heather Havrilesky"Besieged by 'Friends'" -- / Mario Vargas Llosa"The Culture of Liberty" -- / Jamaica Kincaid"On Seeing England for the First Time" -- The Clash of Civilizations: Is Conflict Avoidable? -- / K. Oanh Ha"American Dream Boat'" -- / Margaret Atwood"When Afghanistan Was at Peace" -- / Dinesh D'Souza"The World in 1500-or the West as a Backwater" -- / Karen Armstrong"Fundamentalism Is Here to Stay" -- / Samuel P. Huntington"The West and the Rest: Intercivilizational Issues" -- / Pippa Norris, Ronald Inglehart"It's the Women, Stupid" -- / Amartya Sen"A World Not Neatly Divided" -- / Edward Said"Andalusia's Journey" -- The Age of Terror: What Is the Just Response? -- / Naomi Shihab Nye"To Any Would-Be Terrorists" -- / Greg Campbell"Blood Diamonds" -- / Peter Carey"Letter from New York" -- / Bill Powell"Generation Jihad" -- / Jeffrey Rosen"Bad Luck: Why Americans Exaggerate the Terrorist Threat" -- / Arundhati Roy"The Algebra of Infinite Justice" -- Global Aid: Can We Reduce Disease and Poverty? -- / Jeffrey Sachs"What I Did on My Summer Vacation" -- / Namrita Talwar"Cities Without Slums" -- / Fareed Zakaria"A Threat Worse Than Terror" -- / Anuradha Mittal"Technology Won't Feed World's Hungry" -- / Kenneth Rogoff"A Development Nightmare" -- / Vivienne Walt, Amanda Bower"Follow the Money" -- / Alison Katz"AIDS in Africa" -- The Fate of the Earth: Can We Preserve the Global Environment? -- / Rachel Carson"The Obligation to Endure" -- / Andy Rooney"Talking Trash" -- / Jared Diamond"Lessons from Lost Worlds" -- / Bill McKibben"Driving Global Warming" -- / Annie Dillard"In the Jungle" -- / Jane Goodall"Digging Up the Roots" -- / Francis Fukuyama"In Defense of Nature, Human and Non-human" -- / Jonathan Schell"A Hole in the World" -- Conducting Research in the New Global Era -- The Research Process -- The Writing Process -- Documentation.
Includes index.
Includes bibliographical references and index.
Keywords: College readers; English language -- Rhetoric -- Problems, exercises, etc; Report writing -- Problems, exercises, etc; Globalization -- Problems, exercises, etc; Readers -- Globalization